PELATIHAN PETUGAS SISTEM PENCATATAN DAN PELAPORAN TERPADU PUSKESMAS DI KABUPATEN TAPANULI SELATAN - Elmina Tampubolon; Friska Ernita Sitorus; Efriza Efriza (INSTITUT KESEHATAN DELI HUSADA, 2021)
The Puskesmas Integrated Recording and Reporting System (SP2TP) is intended to meet administrative needs at higher levels in order to develop, establish policies and be utilized by Puskesmas to improve Puskesmas efforts, through planning, mobilizing, implementing, monitoring, controlling and assessing. The training for SP2TP officers in South Tapanuli Regency is aimed at increasing the capacity and capability of human resources in managing common problems. The training was carried out using the lecture method interspersed with discussions and brain storming to stimulate the training atmosphere. The training participants are invited to express their opinions, especially the problems faced at the puskesmas in managing SP2TP, so that solutions can be found together. Participants were given a question about data processing, in the form of items in the SP2TP format so that it became useful information. This is done so that the absorption of SP2TP material can be maximized so that it can be directly practiced in managing SP2TP problems at their respective health centers.